2019
DOI: 10.1111/nep.13656
|View full text |Cite
|
Sign up to set email alerts
|

Regional Citrate Anticoagulation for Continuous Renal Replacement Therapy ‐ A Safe and Effective Low‐Dose Protocol

Abstract: Aims Regional citrate anticoagulation (RCA) is the preferred mode of anticoagulation for continuous renal replacement therapy (CRRT). Conventional RCA‐CRRT citrate dose ranges from 3 to 5 mmol/L of blood. This study explored the effectiveness of an RCA protocol with lower citrate dose and its impact on citrate‐related complications. Methods This prospective observational study compared two RCA‐CRRT protocols in the intensive care unit. RCA Protocol 1 used an initial citrate dose of 3.0 mmol/L while Protocol 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(51 reference statements)
0
20
0
Order By: Relevance
“…The low incidence of CA in our study was most likely attributed to the low citrate load (27.2 mmol/h) with sufficient patency of the extracorporeal circuit. 30 Furthermore, we adopted a more rigorous diagnosis criteria of CA than the study by Tan et al 12 Morgera et al 31 reported than more than 50% of patients developed metabolic alkalosis during RCA-CRRT. The rate of metabolic alkalosis in our study was significantly lower because the bicarbonate fluid (B fluid) was infused separately and was adjustable in our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The low incidence of CA in our study was most likely attributed to the low citrate load (27.2 mmol/h) with sufficient patency of the extracorporeal circuit. 30 Furthermore, we adopted a more rigorous diagnosis criteria of CA than the study by Tan et al 12 Morgera et al 31 reported than more than 50% of patients developed metabolic alkalosis during RCA-CRRT. The rate of metabolic alkalosis in our study was significantly lower because the bicarbonate fluid (B fluid) was infused separately and was adjustable in our protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In patients without COVID-19, citrate dose may even be lowered to 2.5 mmol/L, which is noninferior to higher citrate dosing for an optimal filter life in general. 32 In addition, we suggest a balance between RCA and heparinization to allow proportionate consumption of both. Importantly, premature filter clotting is commonly observed in patients with COVID-19.…”
Section: Anticoagulation and Filter Lifementioning
confidence: 98%
“…However, we did not modify our RCA regimen, and the circuit ioniccalcium was still achieved with up-titration of citrate flow rate according to a sliding scale. 1 This also suggests that the formulae for correction of Na can be used for different citrated-replacement fluid formulations as long as it is titrated according to the circuit calcium Many other factors may influence serum sodium levels, including urine output, intravenous fluids, and medication diluents. To control urine output, IV desmopressin was administered.…”
Section: Discussionmentioning
confidence: 99%
“…The initial citrate dose was 2.5 mmol/L of blood as per institution protocol which utilized a citrated-replacement fluid containing 140 mmol/L sodium and 18.0 mmol/L citrate (Regiocit, Baxter International Inc., Deerfield, Illinois, USA) administered pre-blood pump. 1 Citrate dose was titrated according to a sliding scale to target a circuit ionized-calcium of 0.26-0.40 mmol/L. A calcium-free dialysate (Biphozyl, Baxter International Inc., Deerfield, Illinois, USA) with 140 mmol/L sodium was employed.…”
mentioning
confidence: 99%